Analisis Pelaksanaan Behavior Based Safety dalam Membentuk Perilaku Aman Tenaga Kerja di Laboratorium Balai Besar Karantina Hewan Ikan dan Tumbuhan Kalimantan Timur - Reynitha Permatasari; Ririn Wulandari; Andini Putri Andini; Ajeng Dwi Zhafira; Frederika Daud; Putri Maharani; Febryna Indira Hartomo; Anis Rohmana Malik (Institut Nalanda, 2024)
The Balikpapan Class 1 Agricultural Quarantine Laboratory is one of the laboratories in Indonesia that has a behavior-based work safety program, namely the Behavior-Based Safety (BBS) program which aims to observe worker behavior. The aim of this research is to obtain an overview of the implementation of Behavior-Based Safety programs at the Balikpapan Class 1 Agricultural Quarantine Laboratory. This research is descriptive qualitative research using direct observation methods and in-depth interviews. The research subjects consisted of 2 informants, 1 key informant, 1 main informant. The research results showed that workers at the Balikpapan Class 1 Agricultural Quarantine Laboratory understood unsafe acts. The implementation of the Behavior-Based Safety (BBS) program has been running well and appropriately.